2016
DOI: 10.1002/2015wr018319
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting hydraulic hysteresis based on long‐term monitoring of hydraulic states in lysimeters

Abstract: Hysteretic processes have been recognized for decades as an important characteristic of soil hydraulic behavior. Several studies confirmed that wetting and drying periods cannot be described by a simple functional relationship, and that some nonequilibrium of the water retention characteristics has to be taken into account. A large number of models describing the hysteresis of the soil water retention characteristic were successfully tested on soil cores under controlled laboratory conditions. However, its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…Despite the present absence of experimental evidence for these explanations, the disentangling of the field data could provide ideas for including the intraseasonal dynamics of soil hydraulic properties in the simulation of the soil water flow (e.g., Alletto et al, 2015). Similarly, Hannes et al (2016) stated that better model representations of the complex dynamics of soil water retention were needed that included a concept of hydraulic nonequilibrium and temporal dynamics of soil structure that lead to changes in hydraulic properties. In this sense, long‐term effects of soil erosion have to be considered; soil profile truncation and a continuous incorporation of subsoil material through plowing in the topsoil (or conversely the deposition of colluvium) may gradually change textural, structural, and soil chemical and biological properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the present absence of experimental evidence for these explanations, the disentangling of the field data could provide ideas for including the intraseasonal dynamics of soil hydraulic properties in the simulation of the soil water flow (e.g., Alletto et al, 2015). Similarly, Hannes et al (2016) stated that better model representations of the complex dynamics of soil water retention were needed that included a concept of hydraulic nonequilibrium and temporal dynamics of soil structure that lead to changes in hydraulic properties. In this sense, long‐term effects of soil erosion have to be considered; soil profile truncation and a continuous incorporation of subsoil material through plowing in the topsoil (or conversely the deposition of colluvium) may gradually change textural, structural, and soil chemical and biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for the main wetting and drying curves, a factor of two was suggested, which was sometimes used as default value in numerical models of soil water flow. The modeling of hysteretic water retention was tested in field studies (e.g., Basile et al, 2003; Canone et al, 2008); however, these models were not able to fully reproduce the dynamic behavior of water retention data under in situ conditions (Hannes et al, 2016). Thus, Hannes et al (2016) suggested grouping observed water retention dynamics in three categories: the hydraulic nonequilibrium, the quasi‐nonequilibrium situation, and the soil structure dynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter can be considered as hydraulic nonequilibrium with a pretty long time scale of equilibration. An impressive collection of long‐term monitoring data for water content and water potential showing hysteresis and hydraulic nonequilibrium was presented by Hannes et al (2016), which is discussed further below. When relating measurements of water content and water potential, the different support volume of the measurements needs to be considered.…”
Section: Scales and Scale Transitions Of Water Dynamicsmentioning
confidence: 99%
“…In general, there are many soil characteristics broadly related to soil composition and structure (including macro‐ and biopores) and also to exogenic processes, including water repellency, wetting and drying, swelling and shrinkage, air entrapment, freeze–thaw, thermal gradients, impermeable layers, and anthropogenic perturbations (e.g., tillage, harvesting) that impact infiltration and runoff at the point scale (see Young and Crawford [2004] and Hannes et al [2016], for example).…”
Section: Improving the Infiltration Process In Land Surface Modelsmentioning
confidence: 99%